ε-mechanism driven pulsations in hot subdwarf stars with mixed H-He atmospheres - Battich Tiara; Bertolami Marcelo M. Miller; Córsico Alejandro H.; Althaus Leandro G. (Open Astronomy, 2017)
The ε mechanism is a self-excitation mechanism of stellar pulsations which acts in regions where nuclear burning takes place. It has been shown that the ε mechanism can excite pulsations in hot pre-horizontal branch stars before they settle into the stable helium core-burning phase and that the shortest periods of LS IV-14º116 could be explained that way.We aim to study the ε mechanism in stellar models appropriate for hot pre-horizontal branch stars to predict their pulsational properties.We perform detailed computations of non-adiabatic non-radial pulsations on such stellar models.We predict a new instability domain of long-period gravity modes in the log g − log Teff plane at roughly 22000 K ≲ Teff ≲ 50000 K and 4.67 ≲ log g ≲ 6.15, with a period range from ~ 200 to ~ 2000 s. Comparison with the three known pulsating He-rich subdwarfs shows that the ε mechanism can excite pulsations in models with similar surface properties except for modes with the shortest observed periods. Based on simple estimates we expect at least 3 stars in the current samples of hot-subdwarf stars to be pulsating by the ε mechanism. Our results could constitute a theoretical basis for future searches of pulsators in the Galactic field.